# Prove that the period of a SHM is 2pi*sqrt(m/k)

1. Feb 17, 2017

### ItsTheSebbe

1. The problem statement, all variables and given/known data
When I was in high school I was thaught that the period of a simple harmonic oscillation (mass on spring, ball on pendulum, etc) was equal to $T=2\pi \sqrt \frac m k$ though they have never explained to me why. That's what I wanted to find out.

So for example, let's take a mass $m$ on a spring with spring constant $k$, give it a little nudge and it will start oscillating in a wave-like manner (let's assume no energy is lost due to friction).

PS: This is the first time I'm trying to use LaTeX (first post in general), so if there's anything wrong with the formatting, please let me know :)!

2. Relevant equations
$T=\frac {2\pi} {\omega}$
$F_{spring}=-kx$
$F_{net}=ma$

3. The attempt at a solution
$F_{net}=F_{spring}$
$ma=-kx$
$m \frac {d^2x} {dt^2} +kx=0$
$\frac {d^2x} {dt^2} +\frac k m x=0$
$\ddot x(t) + \frac k m x(t)=0$

$\text{take} \ \ x=e^{Rt}$

$R^2e^{Rt} +\frac k m e^{Rt}=0$
$R^2+\frac k m =0$
$R^2=-\frac k m$
$R=\pm i\sqrt \frac k m$

$\text{hence, } x(t)=C_1e^{i\sqrt \frac k m t}+C_2e^{-i\sqrt \frac k m t}$

Now, here I get stuck. I know I need to eventually get $x(t)=Acos(\omega t+\phi)$
I don't really understand how to get there; probably by using Euler's formula.
From here on out I can proof the equation, namely:

$\ddot x=-A\omega^2\cos(\omega t+\phi)=-x\omega^2$
$\text{plugging into EoM gives:}$
$-x\omega^2+\frac k m x=0$
$\omega^2=\frac k m$
$\omega=\sqrt \frac k m$
$T=\frac {2\pi} {\omega}=2\pi \sqrt \frac m k$

2. Feb 17, 2017

### James R

Your expression here can be re-written as:
$$x(t) = C_3 \cos(\sqrt{\frac{k}{m}} t) + C_4 \sin(\sqrt{\frac{k}{m}} t)$$
by suitably defining $C_3$ and $C_4$ in terms of $C_1$ and $C_2$ using Euler's formula, as you say.

3. Mar 5, 2017

### ItsTheSebbe

Now how can I get from $x(t) = C_3 \cos(\sqrt{\frac{k}{m}} t) + C_4 \sin(\sqrt{\frac{k}{m}} t)$ to a form of $x(t)=Acos(\omega t+\phi)$?

4. Mar 6, 2017

### ehild

You derived that ω = √(k/m). So you have to prove that C3cos(ωt)+C4sin(ωt)=Acos(ωt+Φ).

Expand the right side, using the addition formula for cosine. cos(α+β)=cos(α)cos(β)-sin(α)sin(β).
α=ωt and β=Φ.
So C3cos(ωt)+C4sin(ωt)=Acos(ωt)cos(Φ)-Asin(ωt)sin(Φ). The equality must hold for all values of ωt which means that the coefficient of both the cosine terms and the sine terms must be equal on both sides.
Or you can think that it must be true ωt=0 and also for ωt=pi/2:
For ωt=0, C3=Acos(Φ).
for ωt=pi/2, C4=-Asin(Φ).

You can find both A and Φ from these equations.